Wheelbarrow livelihoods’, urban space and antinomies of survival in Ibadan, south west Nigeria (2019)
Wheelbarrows are a common sight in Nigerian cities where they function as an instrument of work among the urban poor. This paper explores how the wheelbarrow is increasingly deployed as a ‘mobile shop’, and describes the livelihoods of urban subjects who use it for street trade and space appropriation in Ibadan, Nigeria. Using 30 in-depth interviews, non-participant observation and picture documentary, we analyse how wheelbarrow street traders reconfigure urban space in everyday encounters with space managers who tax and exploit space users. Findings show that marginal urban subjects invest in wheelbarrows and exert personal agency to create ‘wheelbarrow livelihoods’. The participants use the tool to reconfigure urban space access and negotiate ‘presence’ in the city and engage in ‘visibility’ struggles with shop owners. People on the social margins of cities thrive by adopting livelihood strategies that enable them to occupy and maintain a presence in contentious urban spaces.